Development and storage quality evaluation of pandan (Pandamus amaryllifolius) flavored tapioca pearls. - Dalisay, Mariah Maxine Gumboc
Commercially available tapioca pearls uses synthetic food coloring and des not have anay flavor or aroma. Increasing the value and quality of this product led to the development of pandan-flavored tapioca pearls wherein natural flavor and color of pandan in a form of juice extract was used to impart the desired flavor, odor, and color attribute to the product. Three ratios of dried pandan leaves to water were used for boiling to obtain pandan juice extract. The ratios were 20:80 (F1) , 30:70 (F2), and 40:60 (F3) (w/w basis) and these were used to make three different formulations of pandan-flavored tapioca pearls. F3 was the most preferred formulation (MPF) and was characterized for its physical, chemical, proximate, and sensorial properties. Analyses made were water holding capacity, water activity, pH, moisture content, crude ash, crude protein determination, and sensory evaluation. Effect of storage on these properties was also evaluated. Acceptability level of the MPF sample was like moderately, both for cooked and uncooked. Storage has no significant effect on the acceptability level of MPF sample. Addition of pandan juice extract showed an improved in color (very light green), odor (moderate pandan odor), and flavor (strong pandan flavor) of the sample. The difference of the MPF from the control was determined to be very large and found that the difference is due to the characteristic pandan color, odor, and flavor. However, storage decreased these sensory attributes resulting to a decrease in difference of MPF from the control with time. Results showed that addition of pandan juice extract has no effect on the crude protein (0.4479%) and water activity with a value ranging from 0.781 to 0.913, which decreased with time. The moisture content of uncooked sample did not significantly decreased from day 1 having a value of 25.48% to 14.98% at day 14. Moisture of cooked sample, on the other hand, is significantly higher (value is about 80%) than the uncooked sample making it highly perishable. However, addition of pandan juice extract the pH (4.08-5.37), water holding capacity (0.475-0.941 gH2O held/g sample), and ash content (0.5824%) of the sample. Storage increased the WHC and %moisture of cooked samples while decreased the %moisture of uncooked sample. Storage was found to have different effect on each properties of the sample. Also, results suggest that pandan juice extract improved the quality of tapioca pearls.